Lomba Senam Kreasi Sebagai Upaya Meningkatkan Kreatifitas Dan Kebugaran Jasmani - MAHARANI FATIMA GANDASARI; Jack suman rulis manurung; arisman arisman; Ella Anugrarista; erna yantiningsih; noer riswandi; siska riyanti (Jurnal Berkarya Pengabdian Masyarakat, 2021)
Creative gymnastics is exercise created by someone with an aesthetic technique of their own choice, the exercise is not bound to certain aesthetic standards, although in the movement it does not leave the aesthetic characteristics of a gymnastics. The purpose of community service is to introduce creative gymnastics through this virtual creative gymnastics competition as an effort to stimulate creativity and physical fitness of students in universities. Creative Gymnastics will be held on August 25, 2021. The implementation of this community service uses demonstration and competition methods. The competition is held for one day with a time of 4 hours. The competition was participated by National level university students. Activities include a Technical meeting which is then followed by a Virtual Gymnastics competition. The results of this activity were obtained by all active and enthusiastic participants to take part in the activities and instilling the educational values ​​contained therein as well as increasing creativity and physical fitness. Keywords: Creative Gymnastics, Competition, active and Enthusiastic